2019
DOI: 10.1002/cncr.32338
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of probable depression in prostate cancer survivors

Abstract: Background The early diagnosis and treatment of depression are cancer care priorities. These priorities are critical for prostate cancer survivors because men rarely seek mental health care. However, little is known about the epidemiology of depression in this patient population. The goal of this study was to describe the prevalence and predictors of probable depression in prostate cancer survivors. Methods The data were from a population‐based cohort of North Carolinian prostate cancer survivors who were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
45
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 74 publications
5
45
0
7
Order By: Relevance
“…Watts et al identified pretreatment, on-treatment and post-treatment depression rates of 17.27%, 14.70% and 18.44%, suggesting that prevalence of depression in men with PCa, across the treatment spectrum, is relatively high [ 6 ]. With the advances in treatment, there has been an increasing interest about psychological distress in PCa with androgen deprivation therapy [ 11 ] and survivors [ 12 ], but not much is generally known regarding the mental health issues of patients within 18 months after diagnosis of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Watts et al identified pretreatment, on-treatment and post-treatment depression rates of 17.27%, 14.70% and 18.44%, suggesting that prevalence of depression in men with PCa, across the treatment spectrum, is relatively high [ 6 ]. With the advances in treatment, there has been an increasing interest about psychological distress in PCa with androgen deprivation therapy [ 11 ] and survivors [ 12 ], but not much is generally known regarding the mental health issues of patients within 18 months after diagnosis of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Watts et al identi ed pretreatment, on-treatment and post-treatment depression rates of 17.27%, 14.70% and 18.44%, suggesting that prevalence of depression in men with PCa, across the treatment spectrum, is relatively high [6]. With the advances in treatment, there has been an increasing interest about psychological distress in PCa with androgen deprivation therapy [11] and survivors [12], but not much is generally known regarding the mental health issues of patients within 18 months after diagnosis of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a variety of standardized questionnaires have been used to assess sexual function in oncology settings [ 22 ], most of them were specific to only one type of cancer or gender and focused on the physical aspect (erectile function, lubrication in women), ignoring the other SH domains (sexual desire, hugging and kissing, orgasm difficulties). If a cancer treatment causes specific physical SH side effects such as fatigue, incontinence, erectile dysfunction, dyspareunia, problems with arousal, lubrication, and pain [ 6 , 12 ], then psychological consequences, such as a poor body image, depression, and anxiety, should also be prioritized in the care of cancer survivors [ 23 , 24 , 25 ], and could be strongly related to SH when viewed globally rather than through specific symptoms.…”
Section: Introductionmentioning
confidence: 99%